Neo-Aristotelian Metaphysics and the Theology of Nature (Taylor & Francis, 2022)
Philosophy, metaphysics, philosophy of religion, philosophy of mind, philosophy of science, religion and philosophy, religion and science, christian theology
English
Keywords: Philosophy of religion; Philosophy: metaphysics & ontology; Philosophy; Philosophy, metaphysics, philosophy of religion, philosophy of mind, philosophy of science, religion and philosophy, religion and science, christian theology